SYNERGISTIC EFFECT OF DIFFERENT MICRONUTRIENTS ON THE GROWTH OF FUSARIUM OXYSPORUM F.SP. CUBENSE CAUSING PANAMA WILT OF BANANA - A. A. JAGTAP,; C. P. BHAGAT,; M. S. DESAI, (The Bioscan, 2025)
Panama wilt, caused by Fusarium oxysporum f. sp. cubense (Foc), is one of the most devastating diseases affecting banana production worldwide. Micronutrients in soil are significant factors in plant health and disease resistance, as they affect both host-pathogen interactions and fungal growth dynamics. This study investigates the effect of some key micronutrients, such as Manganese, magnesium and boron, on the growth and pathogenicity of Foc. The paper would gain strength, for example by detailing concentrations of micronutrients studied and application methods. This means that it may be made reproducible or comparable to other studies. The inclusion of potential mechanisms on how this micronutrient is affecting growth of fungi and increased resistance by the plant makes the outcome more meaningful. In essence, therefore, this work presents a relevant contribution to the comprehension of relationships between micronutrient-pathogens and provides real practical insights into managing Panama wilt among banana cultivators.